Norway and the polar regions - Hansson, Rasmus (The Royal Norwegian Ministry of Foreign Affairs, 1998)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

The geology and age of Peter I Øy, Antarctica - Prestvik, Tore; Duncan, Robert A (Polar Research, 1991)
The island Peter I Oy is located in the Bellinghausen Sea 400 km off the coast of West Antarctica. It is situated at the transition between oceanic and contintental crust close to a former transform fault, the Tharp fracture zone. The island is completely volcanic, consisting of predominantly alkali basalt and hawaiite and some more evolved rocks. Sampling done by the Aurora expedition in 1987 has made dating and detailed petrological studies possible. The island appears to be much younger (< 0.5 Ma) than previously believed. However, the volcanic activity responsible for this oceanic island may have lasted for 10-20 Ma. Volcanic activity at the island thus took place at the same time as post-subduction rift-related volcanism took place along the Antarctic Peninsula and in Marie Byrd Land. However, the petrologic data indicate that this may be coincidental and that the Peter I Oy activity is independent and related to transtensional rifting along the Tharp fracture zone.
Keywords: Peter I. Øy; geologi; petrologi

I hjertet av Antarktis; Norge i Antarktis - Imbert, Bertrand C; Hem, Arne (Polarforskningens pionerer, 1990)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Norge; Peter I. Øy; Roald Amundsen; Sydpolsekspedisjonen; Sørishavet; hvalfangst; oppdagelsesreiser

Namnemanus Peter I Øy (Norsk Polarinstitutt, 1988)
Pages: Vedtak sak 125, 21.1.1988. Namnekomiteen
Keywords: Peter I. Øy; geografi; kartlegging

Norway's polar territories - Barr, Susan (Aschehoug, 1987)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Peter I. Øy; geografi; geologi; historie; polarområdene; polarpolitikk

Norge i polarområdene - Egeland, Knut (Leif Holtedahls forl., 1982)
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; Nordmenn; Norge; Norsk Polarinstitutt; Peter I. Øy; Sørishavet; geografi; historie; norske ekspedisjoner; oppdagelsesreiser; polarområdene; polarpolitikk

Ornithology of the "Brategg" Expedition - Holgersen, Holger (Hvalfangstmuseet, 1957)
Publication Title: Publikasjon fra Kommandør Chr. Christensens hvalfangstmuseum i Sandefjord. Scientific results of the Brategg Expedition, 1947-48
Keywords: Brategg ekspedisjon; Peter I. Øy; fugler; ornitologi

Range of the Ringed Penguin, Pygoscelis antarctica - Holgersen, Holger (The Auk, 1951)
Publisher: American Ornithological Society
Keywords: Brategg ekspedisjon; Peter I. Øy; fugler; ornitologi

Antarctic pelecypods - Soot-Ryen, Tron (Dybwad, 1951)
Publication Title: Scientific results of the Norwegian Antarctic expeditions 1927-1928 et sqq., instituted and financed by consul Lars Christensen
Keywords: Bouvetøya; Peter I. Øy; bivalvia; bløtdyr; ekspedisjoner; forskning; muslinger; zoologi

Die südpolaren Gebiete - Smedal, Gustav (Souveränitätsfragen der Polargebiete : norwegische Interessen in den Eismeeren, 1943)
Keywords: Antarktis; Bouvetøya; Norge; Peter I. Øy; internasjonal; polarområdene; politikk; rett

Oppdeling av polatraktene - Hoel, Adolf (Norge i Ishavet, 1941)
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; internasjonal politikk; polarområdene

Sydishavet - Hearst Land, Charcot ö (Blad 4) (Hvalfangernes Assuranceforening, 1937)
Pages: Blad 4 Place: Sandefjord
Keywords: Norvegia ekspedisjoner; Peter I. Øy; Sørishavet; geografi; kartlegging

Lov om Bouvet-øya, Peter I's øy og Dronning Maud Land m.m. (bilandsloven) (Lovdata, 1930)
Volume: 1930-02-27-3 Place: Oslo
Keywords: Bouvetøya; Dronning Maud Land; Peter I. Øy; jus; lovgivning

The Antarctic (The Geographical Journal, 1930)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; Bouvetøya; Christen Christensen; Hjalmar Riiser; Larsen; Norvegia ekspedisjonen; Peter I. Øy; kartlegging; oppdagelsesreiser

Antarctic whaling and exploration - Aagaard, Bjarne (Scottish Geographical Magazine, 1929)
Keywords: Odd I.; Peter I. Øy; Sørishavet; ekspedisjonen; ekspedisjoner; historie; hval; hvalfangst

Peter I Øy - Larsen, Nils (1929)
Pages: ved Nils Larsen, Norvegia-Ekspedisjonen 1928-1929 Place: Oslo
Keywords: Lars Christensen; Norvegia ekspedisjonen; Peter I. Øy; geografi; kartlegging

Die norwegische Peter-I.-Insel - Sachse, Walter (Dr. A. Petermann's Mitteilungen aus Justus Perthes' Geographischer Anstalt, 1929)
Publisher: Perthes Place: Gotha
Keywords: Odd I; Peter I. Øy; ekspedisjonen; geografi; oppdagelsesreiser

Fra det norske forskningsarbeide i de vest-antarktiske strøk syd-sommeren 1927—28 - Holtedahl, Olaf (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1928)
Publisher: Routledge
Keywords: Lars Christensen; Odd I; Peter I. Øy; ekspedisjonen; geografi; kartlegging

Trekk av Sydishavets dyreliv - Olstad, Ola (Norsk Geografisk Tidsskrift - Norwegian Journal of Geography, 1928)
Publisher: Routledge
Keywords: Antarktis; Bouvetøya; Lars Christensen; Norvegia ekspedisjoner; Peter I. Øy; dyreliv; forskning; zoologi

Gesteine von der Peter I. - Insel, West-Antarktis - Broch, Olaf Anton (Dybwad, 1927)
ISBN: 05497019
Keywords: Odd I; Peter I. Øy; ekspedisjonen; geologi; petrografi